2019
DOI: 10.4103/jispcd.jispcd_119_18
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration with enamel matrix derivative in the management of generalized aggressive periodontitis: A case report with 11-year follow-up and literature review

Abstract: Objectives: Aggressive periodontitis (AgP) represents an uncommon but rapidly advanced inflammatory process, which involves the destruction of periodontal tissues. This study aimed to report a case of generalized AgP (GAgP), where the treatment approach consists of the utilization of the full-mouth disinfection protocol (FMDP) in conjunction with flap curettage and regenerative appliance of enamel matrix derivatives (EMDs). The associated literature was also reviewed. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A bone substitute and enamel matrix derivative were used to repair the buccal plate extraction socket [ 28 ]. Additionally, it was hypothesized that using an enamel matrix derivative could help patients whose inflammatory processes were fast progressing and causing the degeneration of periodontal tissue [ 29 ]. Additionally, severe intrabony flaws linked with the palatal radicular groove were successfully treated without endodontic therapy or retreatment by applying an enamel matrix derivative [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A bone substitute and enamel matrix derivative were used to repair the buccal plate extraction socket [ 28 ]. Additionally, it was hypothesized that using an enamel matrix derivative could help patients whose inflammatory processes were fast progressing and causing the degeneration of periodontal tissue [ 29 ]. Additionally, severe intrabony flaws linked with the palatal radicular groove were successfully treated without endodontic therapy or retreatment by applying an enamel matrix derivative [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that periodontitis is associated with the initiation or progression of various systemic diseases, such as cardiovascular and chronic kidney disease and diabetes (6)(7)(8). Although progress has been achieved in the treatment of periodontitis, including skin flap curettage, scaling and root planting, the effects of the aforementioned therapies only control the development of this condition (9)(10)(11). Therefore, it is of clinical importance to investigate promising therapeutic agents for periodontitis to improve oral health and avert the development of systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of regenerative medicine and tissue engineering technology, the focus of periodontitis treatment has shifted from the control of soft tissue inflammation to the control of pathological bone loss, so as to achieve periodontal tissue regeneration [6][7][8]. At present, a variety of regeneration methods have been proposed to treat periodontitis, including guided tissue regeneration, application of platelet-rich plasma, enamel matrix derivative and so on [9][10][11]. However, most of these treatment methods have shown variable and unpredictable clinical results.…”
mentioning
confidence: 99%